The dark side of regionalism: how regional organizations help authoritarian regimes to boost survival. Issue 2 (17th February 2021) - Debre, Maria J.
ABSTRACT: The international dimension of authoritarian resilience is receiving increased attention by scholars of comparative politics and international relations alike. Research suggests that autocratic states exploit regionalism to boost domestic regime security. This article explains how membership in regional organizations can help to strengthen survival chances of autocratic incumbent elites. It argues that membership provides additional material, informational, and ideational resources to autocratic incumbents that can be used to boost domestic survival strategies vis-à-vis internal and external challengers. The article provides qualitative case-based evidence to show how autocratic incumbents in Zimbabwe, China, and Bahrain have benefited from the involvement of regional organizations during moments of political instability to strengthen legitimation, repression, co-optation, and international appeasement strategies. The article thereby provides the first encompassing explanation linking regionalism and authoritarian survival politics that is applicable across regions and different types of authoritarian regimes.